Syntactic complexity in Iranian learners' English writing and speaking - Sarah Yazdani (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2018)
This study is aimed at demonstrating the use of syntactic complexity in Iranian learners’ English written and spoken discourse using quantitative-qualitative approach. To fulfill this purpose, forty-five female Iranian students from 3 branches of a private language institute in Mashhad were recruited. The subjects were divided into three groups based on Cambridge Placement Test results: elementary, intermediate, and advanced. All groups (each 15 participants) were asked to write a 200-word essay on a topic. Thereafter, the essays were examined manually for the T-units according to the classification used by the experts. In the follow-up phase of the study, participants were asked to attend an interview on the same topic of their writings to evaluate the usage of C-units in their speaking. The findings illustrate the fact that the most frequent element in macro level was clause in both writing and speaking, while in micro level, there were significant differences between elementary group & intermediate group and between the elementary group and advanced group in writing skill and there was a significant difference between elementary group & advanced group in using subordinate clauses in speaking. A future study investigating syntactic complexity in other skills such as reading would be very interesting.